Design Of A Patient Information System For Covid – 19 Using PHP At Mukomuko Hospital - Adinda Trisista; Ujang Juhardi; Guntur Alam; Yuza Reswan (Jurnal Komputer, Informasi dan Teknologi, 2023)
The design of a COVID-19 patient information system using PHP Muko-muko Hospital has been successfully created which includes patient identity data confirmed for COVID-19, clinical information for COVID-19 patients, monitoring information for confirmed COVID-19 patients, and reports on COVID-19 patient data. -19. This system has been neatly designed to make it easier for officers to find data on COVID-19 patients who have been monitored or have not been monitored when applied to the real system.